DROUGHT MANAGEMENT OF COCONUT HOLDINGS - Dr. D. V. Liyanage (International Coconut Community, 1993)
Prolonged droughts retard growth of coconut palms and reduce production. Current systems of chemical farming in coconut holdings do not mitigate adverse drought effects on palms. They should be replaced with bio‑farming techniques, which will result in improvement of structure, water holding capacity and fertility of the soil, thereby delaying onset of soil moisture stress during dry seasons. With the drought management practices based on mulching bio-farming, soil nutrients are released gradually so that coconut production is sustained at a high level without much fluctuations through‑out the years. Further, that technology is simple and large investments are not necessary, particularly application of the Coconut/Gliricidia model. Cost of production of coconuts is reduced with bio‑farming.